Mesenchymal Stem Cell Therapy: Hope for Patients With Systemic Lupus Erythematosus - Li, Aifen; Guo, Fengbiao; Pan, Quanren; Chen, Shuxian; Chen, Jiaxuan; Liu, Hua-feng; Pan, Qingjun (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. Although previous studies have demonstrated that SLE is related to the imbalance of cells in the immune system, including B cells, T cells, and dendritic cells, etc., the mechanisms underlying SLE pathogenesis remain unclear. Therefore, effective and low side-effect therapies for SLE are lacking. Recently, mesenchymal stem cell (MSC) therapy for autoimmune diseases, particularly SLE, has gained increasing attention. This therapy can improve the signs and symptoms of refractory SLE by promoting the proliferation of Th2 and Treg cells and inhibiting the activity of Th1, Th17, and B cells, etc. However, MSC therapy is also reported ineffective in some patients with SLE, which may be related to MSC- or patient-derived factors. Therefore, the therapeutic effects of MSCs should be further confirmed. This review summarizes the status of MSC therapy in refractory SLE treatment and potential reasons for the ineffectiveness of MSC therapy from three perspectives. We propose various MSC modification methods that may be beneficial in enhancing the immunosuppression of MSCs in SLE. However, their safety and protective effects in patients with SLE still need to be confirmed by further experimental and clinical evidence.